2020
DOI: 10.4209/aaqr.2020.05.0226
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of COVID-19 on Variations of SO2, NO2, CO and AOD over East China

Abstract: The COVID-19 (Coronavirus Disease 2019) broke out in the late of 2019. On January 23 in Wuhan, and later in all other cities of the country, there were taken measures to control the spread of the virus through quarantine measures. This article focused on East China and attempted to assess comprehensively the environmental impact of the COVID-19 outbreak. This study analyzed satellite observational data of sulfur dioxide (SO 2), nitrogen dioxide (NO 2), carbon monoxide (CO) and aerosol optical depth (AOD) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 36 publications
8
108
0
3
Order By: Relevance
“…The impact of COVID-19 on air quality was also addressed in different Cities of central China by Xu et al (2020a;2020b) evidencing on February 2020 a 30-60 % reduction of the concentration levels of PM2.5, PM10, SO2, CO, and NO2 and a slight increase of 4-14 % of the O3 concentration with respect to the values observed in the same month of the previous three years 2017-2019. Satellite observational data of SO2, NO2 and CO referred to the East of China (Filonchyk et al, 2020) confirmed the air quality improvement during lockdown with average levels reduced by about 30 %, compared with the same period in 2019. Effects of lockdown on air quality were also reported by exploiting local data provided by monitoring stations in India (Mahato et al, 2020;Sharma et al, 2020).…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…The impact of COVID-19 on air quality was also addressed in different Cities of central China by Xu et al (2020a;2020b) evidencing on February 2020 a 30-60 % reduction of the concentration levels of PM2.5, PM10, SO2, CO, and NO2 and a slight increase of 4-14 % of the O3 concentration with respect to the values observed in the same month of the previous three years 2017-2019. Satellite observational data of SO2, NO2 and CO referred to the East of China (Filonchyk et al, 2020) confirmed the air quality improvement during lockdown with average levels reduced by about 30 %, compared with the same period in 2019. Effects of lockdown on air quality were also reported by exploiting local data provided by monitoring stations in India (Mahato et al, 2020;Sharma et al, 2020).…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…Studies performed in various territories of China have demonstrated that stringent COVID-19 control strategies substantially decreased intensities of certain toxins excluding ozone [35,36]. Due to the restrictions on economic and transport activities, the associated emissions decreased with the most considerable reduction in CO (20-36%) and NO 2 (30-52.8%) [36,37]. Moreover, in China, due to the COVID-19 pandemic, the economic slowdown has also resulted in as minimum as 25% drop in carbon dioxide (CO 2 ) discharges later in January, which accounted for a total 6% drop in worldwide emissions [32].…”
Section: Resultsmentioning
confidence: 99%
“…The lockdown policy is believed to have yielded great reductions in air pollutants, especially in China, and thus it provides a favorable opportunity to assess the impacts of anthropogenic sources on air quality in urban agglomerations. Many studies have revealed that air pollutants including aerosol optical depth (AOD), particle matter (PM), nitrogen dioxide (NO 2 ) and carbon monoxide (CO) decreased significantly during the global lockdown, while the secondary pollutant O 3 increased ( Filonchyk et al, 2020 ; Kerimray et al, 2020 ; Nakada and Urban, 2020 ; Wang et al, 2020c ). These related studies were more directed at satellite and ground-based routine data, and observations of aerosol chemical compositions have rarely been investigated to date.…”
Section: Introductionmentioning
confidence: 99%